1984 Olympics Track and Field Competition at Los Angeles Coliseum - Watkins, Howard::::::::: (1984)
Close up of restart of runners leaving starting blocks for Men's 400 meter hurdles Round 1, Heat 1; Edwin Moses in lane 5 off first